1997
DOI: 10.1159/000237475
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Production in Response to Stimulation with Tetanus Toxoid, <i>Mycobacterium tuberculosi</i><i>s</i> and Influenza Antigens in Peripheral Blood Mononuclear Cells and T Cell Lines from Healthy Elderlies

Abstract: Little is known about the type 1/type 2 T cell dichotomy in old age. Peripheral blood mononuclear cells (PBMC) and T cell lines from old and young healthy individuals were therefore analyzed for their production of interferon gamma (IFN-γ) and interleukin 4 (IL-4). Tetanus toxoid (TT), purified protein derivative of Mycobacterium tuberculosis, inactivated influenza virus and OKT-3 were used as stimuli. RT-PCR and ELISA determinations were performed. When stimulated with TT, PBMC from young and old individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
1
9
1
Order By: Relevance
“…This is in accordance with reports from previous studies [23, 24], where it was found that repeated antigenic stimulation was required to elicit significant IL-4 secretion under in vitro conditions when using primary cultures of T cells. This is in contrast to the findings in T cell lines, where there was pronounced IL-4 production in response to antigens [25]. …”
Section: Discussioncontrasting
confidence: 99%
“…This is in accordance with reports from previous studies [23, 24], where it was found that repeated antigenic stimulation was required to elicit significant IL-4 secretion under in vitro conditions when using primary cultures of T cells. This is in contrast to the findings in T cell lines, where there was pronounced IL-4 production in response to antigens [25]. …”
Section: Discussioncontrasting
confidence: 99%
“…Stimulation of PBMCs with non-specific stimuli such as mitogens, anti-CD3, or the superantigen TSST resulted in age-related decreased IFNy production in three cases [18,35,36], no difference in another four cases [31,38,39,40] and an increase in two cases [37,Bernstein,et al submitted]. The four studies using the largest number of subjects [31,35,38, Bernstein et al submitted] all used PBMCs from healthy elderly subjects that were stimulated with PHA, and still reported three different outcomes.…”
Section: Ifn7mentioning
confidence: 99%
“…In three of the studies evaluating PBMC stimulation with specific stimuli, two reported no significant agerelated changes in IFNyproduction [27,40]. The largest study, in which 270 elderly were evaluated for IFNy production in response to trivalent subvirion influenza vaccine before and after vaccination, indicated that the elderly produced significantly lower I FNylevels both preand post-vaccination [41].…”
Section: Ifn7mentioning
confidence: 99%
See 1 more Smart Citation
“…Taking these findings into consideration, an etiologic relationship between the influenza A virus infection and the development of HUS is highly probable in our patient. Inactivated influenza virus has been reported to stimulate interferon production by peripheral blood mononuclear cells [39], and interferon therapy is known to cause HUS-like glomerulopathy [40]. Although the precise mechanisms by which influenza virus triggers HUS have not been elucidated, an altered immune system following viral infection may be responsible.…”
Section: Discussionmentioning
confidence: 99%